2017
DOI: 10.24221/jeap.2.2.2017.1202.115-124
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and physiology of Lactobacilli: a review

Abstract: The consumption of probiotic microorganisms in fermented products has been used for centuries. Lactobacillus spp. is one of the main species studied due to its various beneficial effects on health. This species has a great ability to adapt to hostile environments, produces antimicrobial substances capable of destroying or inhibiting the growth of pathogenic bacteria, and is involved in the digestion of complex carbohydrates not digested by the host. However, there are still some uncertainties and disag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 90 publications
0
12
0
3
Order By: Relevance
“…Lactobacillus colonizes the proximal and distal regions of the porcine digestive tract soon after birth and is one of the core genera in the gastrointestinal tracts of pigs (Mesquita et al, ; Valeriano, Balolong, & Kang, ). Many studies have revealed that Lactobacillus has the potential to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota (Hou, Zeng, Yang, Liu, & Qiao, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus colonizes the proximal and distal regions of the porcine digestive tract soon after birth and is one of the core genera in the gastrointestinal tracts of pigs (Mesquita et al, ; Valeriano, Balolong, & Kang, ). Many studies have revealed that Lactobacillus has the potential to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota (Hou, Zeng, Yang, Liu, & Qiao, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding habits have important implications for intestinal microbiota. In previous studies, food type influenced gut microbiota, which consisted of more biliary metabolic dominant microflora in people with a meat rich diet 3,21 . In contrast, gut microbiota consisted more polysaccharides bacteria in people with a vegetable rich diet 23 .…”
Section: Discussionmentioning
confidence: 94%
“…Further research is needed to investigate the variation of normal intestinal microbial environments that depend on aging-related nutritional features, metabolic activity and associated disorders. There are different types of microorganisms per person, but adult's intestinal microbiotas are relatively stable in healthy people 3 . Metabolism, fermentation, methane processing, oxidizing phosphorus reaction and synthesis of lipopolysaccharide are reactions that combine many things 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations